Effect of platelet rich plasma in non surgically treated chronic Achilles tendon ruptures - Paolo Lorenzon, MD; Enrico Scalco, MD; Michele Scomazzon, MD (Foot & Ankle Surgery: Techniques, Reports & Cases, 2023)
Background: Achille's tendon ruptures are relatively common among foot and ankle injuries. They are considered chronic when last beyond 4-6 weeks from the time of injuries. The management of chronic ruptures is usually different from the acute ones, and although the optimal treatment is controversial, it is common opinion that surgical treatment is the main stay of therapy. Platelet rich therapies are becoming of common use in clinical practice to treat musculotendinous injuries and in some cases, platelet rich plasma has been used as additional therapy when surgery is performed. In this study, we propose the results of a small clinical series in which PRP is used as main treatment in chronic Achille's tendon ruptures. Methods: Between May 2020 and March 2022, five patients with chronic Achille's tendon rupture underwent platelet rich therapy in association with the use of a functional ankle bracing system with wedges for the first 8 weeks. Pre- and post-treatment data were collected with ATRS and AOFAS scores as primary outcomes and heel rise tests as secondary outcomes. Results: there was relevant improvement from pre-treatment to post-treatment clinical and functional outcomes. The AOFAS mean scores gradually improved from 54 in pre-treatment to 100 in post-treatment follow-up (p < 0,001). Heel rise and height significantly increased at the final follow-up. Also, ATRS increased from 23 to 98 at the last follow-up. Conclusion: to our knowledge, this is the first report on PRP use without surgical treatment of a chronic and complete rupture of Achille’s tendon. The reported outcomes (ATRS AOFAS) evidence an improvement during follow-up; the results are in line with those expected after surgical treatment indeed, patients return to their work and sport activity practised before the injury. Level of Evidence: IV, prospective case series